Reinforcement Kompetensi Guru dalam Meningkatkan Kualitas Pembelajaran - Mohammad Zaini (FALASIFA : Jurnal Studi Keislaman, 2020)
This article aims to describe the reinforcement of teacher competence is a continuous thing to do in sustainability because it is about mastery of the learning process in the school. Learning is helping students gain a variety of experiences, so that students' behavior increases, both quantity and quality. The experience includes knowledge, skills and values or norms that serve as controlling attitudes and behaviors. Learning is done by setting up a variety of interactions that exist in and around learning moments that include effective learning elements that influence student success. Good learning according to the Gestalt tradition, which is an attempt to give the subject matter in such a way that students more easily organize it (organize it) into a meaningful pattern.